Psychometric Properties of Pain Intensity Scales Comparing Among Postoperative Adult Patients, Elderly Patients Without and With Mild Cognitive Impairment in China - Yinghua Zhou (Prince of Songkla University, 2011)
Thesis (M.Sc., Nursing Science)--Prince of Songkla University, 2010